IDENTIFIKASI DAMPAK LINGKUNGAN PADA PROSES PENGOLAHAN LUMPUR TINJA (IPLT) JABON DENGAN METODE LIFE CYCLE ASSESSMENT (LCA) - Naniek Ratni J.A.R; Iman Maulana (EnviroUS, 2022)
Sludge treatment at the IPLT is an advanced treatment activity the sewage sludge in the septic tank is not suitable for disposal to the environment because it still contains organic a high. The Jabon Sidoarjo IPLT is the object of research and aims to determine the environmental impact caused by the sewage sludge treatment process at the Jabon Sidoarjo IPLT using the Life Cycle Assessment (LCA) Method. Life cycle assessment (LCA) is used to conduct an environmental impact assessment using the Impact 2002+ method and using a gate to gate approach. The data for each processing process was analyzed with SimaPro 9.0 software. The three biggest contributions of the LCA analysis on the sewage treatment process are non-renewable energy, global warming, and respiratory inorganics. The recommended alternative improvement programs are the application of green buildings in the area around the processing plant, the use of inverters in an effort to save electricity, regular monitoring of cleaning or updating of the processing unit.